Three decades of decentralisation in Ghana: operationalisation of sub-district structures in three selected regions - John Victor Mensah; David Wellington Essaw; Musah Dankwah; Adom Baisie Ghartey; Charles Asare Bamfo (Cogent Social Sciences)
Ghana is a constitutional republic with national and local spheres of government. The 1992 Constitution and other legislative instruments enjoin the practice of decentralised local governance system in the country. Since 1988, the current form of decentralisation has been practised where the sub-district structures comprising Urban, Town, Area, Zonal (UTAZ) Councils and Unit Committees are expected to operate as the effective link between the Metropolitan, Municipal, and District Assemblies (MMDAs) and the communities. This study set out to examine the operationalisation of the UTAZ Councils in three out of the 10 regions in the country. The study employed the descriptive survey design and sampled 304 UTAZ Councils from 57 MMDAs. It revealed that the majority of the UTAZ Councils were operating in permanent office accommodations and chalked achievements in the areas of public education, revenue mobilisation, improvement in environmental sanitation, and the provision of other social services. However, the Councils faced challenges including inadequate staff, poor logistics and infrastructure, low capacity of staff, low revenue base, and insecurity. The study recommends redeployment of some MMDA staff to the UTAZ Councils, improvement in infrastructure and logistics, adequate capacity building, and provision of adequate funds to enhance their operations.